Respuesta :
Answer:
X = -1
Step-by-step explanation:
Rewrite equations:
y = -x + 2; 5x + 2y = 1
Step: Solve y = -x + 2y = 1 for y:
y = -x + 2
Step: Substitute -x + 2 for y in 5x +2y =1 :
5x +2y = 1
5x +2 (-x+2) =1
3x + 4 =1 (simplifiy both sides of the equation)
3x + 4 + - 4 = 1 + -4
(Add -4 to both sides)
3x = -3
3x/3 = -3/3 (Divide both sides by 3)
x = -1
Plug in y to equation
Distribute
Subtract 4 on each side
Add like terms
Divide
Plug in x to y equation
Distribute add like terms
Distribute
Subtract 4 on each side
Add like terms
Divide
Plug in x to y equation
Distribute add like terms
![Ver imagen avastine](https://us-static.z-dn.net/files/ddd/453dc63b02815d4e4afe11fe7c0ab611.png)